Microfiltration Membranes Modified with Zinc by Plasma Treatment - Joanna Kacprzyńska-Gołacka; Monika Łożyńska; Wioletta Barszcz; Sylwia Sowa; Piotr Wieciński (Membranes, 2023)
Polymer membranes play an important role in various filtration processes. The modification of a polyamide membrane surface by one-component Zn and ZnO coatings and two-component Zn/ZnO coatings is presented in this work. The technological parameters of the Magnetron Sputtering-Physical Vapor Deposition method (MS-PVD) for the coatings deposition process show an impact on the influence on the membrane’s surface structure, chemical composition, and functional properties. The characterization of surface structure and morphology were analyzed by scanning electron microscopy. In addition, surface roughness and wettability measurements were also made. For checking the antibacterial activity, the two representative strains of bacteria Escherichia coli (Gram-negative) and Staphylococcus aureus (Gram-positive) were used. The filtration tests showed that polyamide membranes covered with three types of coatings, one-component Zn coatings, ZnO coatings, and two-component Zn/ZnO coatings, presented similar properties. The obtained results show that using the MS-PVD method for modification of the membrane’s surface is a very promising perspective in the prevention of biofouling.